Validated RP-HPLC Method for Simultaneous Estimation of Atenolol, Hydrochlorothiazide and Losartan Potassium in Bulk and Pharmaceutical Dosage Form - Eswarudu, M. M.; Sakheena, P.; Lahari, K.; Babu, P. Srinivasa; Eswaraiah, M. Chinna (Asian Journal of Pharmaceutical Research and Development, 2021)
A simple, specific, accurate, and precise reverse phase high performance liquid chromatographic (RP-HPLC) method was developed for the simultaneous estimation of Atenolol, Hydrochlorothiazide and Losartan potassium in bulk and pharmaceutical dosage form. The separation was carried out using Hypersil C18, 250 ×4.6 mm, 5µm column with mobile phase consisted mixture of Acetonitrile and Potassium dihydrogen ortho phosphate buffer in the ratio of 40:60 (V/V) delivered at a flow rate of 1.5 mL / min and effluents were monitored at 225 nm. The selected chromatographic conditions were effective separation of these drugs. And the retention times of Atenolol, Hydrochlorothiazide and Losartan potassium were found to be 1.46, 2.21 and 3.30 min respectively. The proposed method was found to be linear in the range of 50-150 μg/mL,12.5-37.50 μg/mL, and 50-150 μg/mL for Atenolol, Hydrochlorothiazide and Losartan potassium respectively. The recovery of drugs was found to be 97.56 %, 97.72 % and 98.06 % respectively. The proposed method was validated as per ICH guidelines and it was found to be accurate, precise and robust, and it was applied to the estimation of Atenolol, Hydrochlorothiazide and Losartan potassium in combined tablet dosage form and it can also be used for routine quality control analysis of these drugs in biological samples either alone or in combined pharmaceutical dosage forms.